Brilliant Math Contest

Algebra Level 5

To celebrate the new year, the Brilliant society decided to host a math contest. The results were fantastic, and Brilliant decided to award the top n n students with a medal ( n > 1 ) (n>1) . For the first round, Brilliant awarded it to the top student, along with 1 / 7 {1}/{7} of the remaining students (i.e. n 1 n-1 of them).
For the second round, Brilliant awarded it to the remaining top two students, along with 1 / 7 1/7 of the remaining students.
This process continued, until the k t h k^{th} award, which was awarded to the remaining top k k students. However, at this point in time, there were no more medals left.

How many students won a medal? (a.k.a. what is the value of n n ?)


The answer is 36.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Trongnhan Khong
Oct 15, 2015

Hi,

Let's consider the sequence { u m } \left\{ { u }_{ m } \right\} defined by the recursive formula:

{ u 1 = 1 + 1 7 ( n 1 ) u m = m + 1 7 ( n j = 1 m 1 u j m ) f o r m = 2 , 3 , 4 , . . . \begin{cases} { u }_{ 1 }=1+\frac { 1 }{ 7 } (n-1) \\ { u }_{ m }=m+\frac { 1 }{ 7 } (n-\sum _{ j=1 }^{ m-1 }{ { u }_{ j } } -m)\quad for\quad m=2,3,4,... \end{cases}

(For m k m\le k , u m { u }_{ m } represents the number of medals that was awarded in the m t h { m }^{ th } round.)

u m + 1 = 6 7 ( u m + 1 ) f o r m = 1 , 2 , 3 , . . . \Rightarrow { u }_{ m+1 }=\frac { 6 }{ 7 } ({ u }_{ m }+1)\quad for\quad m=1,2,3,...

Now, we construct a new sequence { v m } \left\{ { v }_{ m } \right\} defined by v m = u m 6 f o r m = 1 , 2 , 3 , . . . { v }_{ m }={ u }_{ m }-6\quad for\quad m=1,2,3,...

v m + 1 = 6 7 v m \Rightarrow { v }_{ m+1 }=\frac { 6 }{ 7 } { v }_{ m }

v m = v 1 ( 6 7 ) m 1 \Rightarrow { v }_{ m }={ v }_{ 1 }{ \left( \frac { 6 }{ 7 } \right) }^{ m-1 }

We know that u k = k { u }_{ k }=k , so v k = k 6 = v 1 ( 6 7 ) k 1 { v }_{ k }=k-6={ v }_{ 1 }{ \left( \frac { 6 }{ 7 } \right) }^{ k-1 } . Let's call it ( 1 ) (1) .

The problem here is to solve ( 1 ) (1) for ( k , v 1 ) Z > 0 × Z (k,{ v }_{ 1 })\in { { Z } }_{ >0 }\times { Z }

Though k = 1 v 1 = 5 k=1\Rightarrow { v }_{ 1 }=-5 satisfies the conditions, it leads to n = 1 n=1 which we don't expect here.

So we look for a value of k > 1 k>1 , ( 1 ) v 1 = 7 k 1 ( k 6 ) 6 k 1 (1)\Rightarrow { v }_{ 1 }=\frac { { 7 }^{ k-1 }(k-6) }{ { 6 }^{ k-1 } } , together with g c d ( 6 , 7 ) = 1 gcd(6,7)=1 we can deduce that k 6 6 k 1 \frac { k-6 }{ { 6 }^{ k-1 } } must be an integer.

However, it can be proved that 0 k 6 6 k 1 < 1 f o r k 2 0\le \left| \frac { k-6 }{ { 6 }^{ k-1 } } \right| <1\quad for\quad k\ge 2 . Thus, the only way that v 1 { v }_{ 1 } is an integer is k = 6 v 1 = 0 v m = 0 u m = 6 n = 36 k=6\Rightarrow { v }_{ 1 }=0\Rightarrow { v }_{ m }=0\Rightarrow { u }_{ m }=6\Rightarrow n=36

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...